KONTRIBUSI KETERAMPILAN MEMBACA PEMAHAMAN TEKS CERPEN TERHADAP KETERAMPILAN MENULIS TEKS CERPEN SISWA KELAS XI SMAN 7 PADANG - Ramadani, Putri; Ratna, Ellya; Hafrison, Mohammad (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACT This article has written the contribution of reading comprehension ability of short story text toward the students’ writing short story text ability at XI class of SMAN 7 Padang. This research is quantitative research using the descriptive method and the contribution research design. The research data is the test result score of reading short story text ability and the test result score of writing short story text ability. The data has obtained through two types of test that are the objective test which uses yo measure the writing ability of short story text. Based on the result of data analysis and the discussion, the researcher concludes the three things follow; first, the average score of the student’ reading comprehension ability of short story text at XI class of SMAN 7 Padang is in the good qualification (78,29). Second, the average score of the student’ writing ability of short story text at XI class of SMAN 7 Padang is in the good qualification (75,89). Third, there are the significant contributions between the reading comprehension ability of short story text toward the students writing ability of story text at XI class of SMAN 7 padang as much as 70,56%.   Kata Kunci: kontribusi, keterampilan, membaca pemahaman, menulis, teks cerpen